Diagnostic and prognostic significance of different mucin expression, preoperative CEA, and CA-125 in colorectal carcinoma: A clinicopathological study - Jain, Parul (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Colorectal carcinoma (CRC) is the fourth most commonly diagnosed malignant disease worldwide, with over 1 million new cases and approximately 5,00,000 deaths each year. AIMS AND OBJECTIVES: This prospective observational study was done to study the clinicopathological characteristics of CRC including mucin stains and correlate the preoperative serum carcinoembryonic antigen (CEA) and cancer antigen (CA)-125 levels with the prognosis. MATERIALS AND METHODS: A total of 90 CRCs were included from December 2010 to June 2013. Detailed history and relevant clinical/radiological findings were noted in all clinically and/or radiologically suspected cases of CRC. Preoperative blood samples were collected for serum CEA and CA-125 level estimation. The mucin expression was evaluated with special stains. RESULTS: The combined Alcian blue-periodic acid Schiff (PAS) staining was positive for both stains in 68.88% cases indicating that both neutral and acidic mucins are increased in CRC. High preoperative serum CEA levels were seen in 82.22% cases, whereas preoperative serum CA-125 levels showed an increase in 20% cases. Higher levels of these tumor markers corresponded with higher TNM stage. CONCLUSIONS: Mucin evaluation in CRCs remains one of the valuable methods as mucinous variants correlate with worse prognosis. Preoperative serum CEA level assessment is an indispensible adjunct to the diagnosis and prognosis of CRC. However, preoperative serum CA-125 level measurement is not an efficient tool for prognostication in CRC and should not be recommended for routine use.